Dampak Covid-19 Terhadap Ekonomi Indonesia - Fakhrul Rozi Yamali; Ririn Noviyanti Putri; Fakhrul Rozi Yamali (Ekonomis: Journal of Economics and Business, 2020)
Since the beginning of 2020 precisely in March, Indonesia has been horrified by one of the phenomena that is the covid-19 pandemic. As of August 2020, the total number of cases in Indonesia was 165,887 with 7,169 deaths in 34 provinces. The spread and increase in the number of covid-19 cases occurred at a very rapid time will have an impact on indonesia's economic downturn. This research aims to find out the policies that have been done by the government to deal with the current outbreak and see the economic impact that occurs in Indonesia. This research shows that policies made by the government in the handling of covid-19 can indirectly lead to a slowdown in economic growth in Indonesia. The impact on the economic sector due to the covid-19 pandemic in Indonesia, among others, layoffs, the onmath of Indonesia's MANUFACTURING PMI, the decline in imports, the increase in prices (inflation) as well as losses in the tourism sector caused a decrease in occupancy. As a result of this, the Indonesian government is expected to be more efficient in addressing the economic downturn in Indonesia resulting from the covid-19 pandemic.